Intimate partner violence and women's economic insecurity - Resko, Stella M. (Criminal justice: recent scholarship, 2010)
Universal risk ideology and intimate partner violence -- Women's economic well-being and intimate partner violence -- Theoretical perspectives on intimate partner violence -- Survey research on intimate partner violence -- "Fragile families" and intimate partner violence -- Male-to-female physical violence within urban families -- Male-to-female coercive control within urban families